Physical properties of keropok (fried crisps) in relation to the amylopectin content of the starch flours - Mohamed, Suhaila; Abdullah, Norakiah; Muthu, Mangayar Karasi (Wiley, 1989)
The physical characteristics of keropok made from various flours (glutinous rice, rice, wheat, sago, tapioca and corn) were studied. The amount of water used to wet the flour in the initial stages of making the keropok was very important, since it affected the linear expansion, oil absorption, elasticity and crunchiness of the resultant fried crisps. Linear expansion, oil absorption and elasticity were positively correlated to the total amylopectin content in the whole flour (r2 = 0.99, 0.97 and 0.97 respectively). The best fitted lines for prediction of linear expansion, oil absorption and elasticity of the fried crisps were 21y ≦ 0.35x ‐ 162, y=0.15x‐ 74 and y=0.0008x‐0.41 respectively, where x is the amylopectin content of the whole flour. Good keropok can be made from any starch‐rich flour that contains a high proportion of amylopectin. These starches can be recognised physically by their clarity on gelatinisation, stability to retrogradation, low resistance to shear and high cold‐paste viscosity. The addition of mung bean flour to tapioca flour helped increase the protein content and flavour of the keropok; it also reduced the oil absorption of the keropok during frying. Although linear expansion decreased with increasing mung bean flour content, the substitution of up to 600 g kg−1 mung bean flour was acceptable since the linear expansion of mung bean/tapioca crisps remained above 35%. The experimental values for linear expansion of mung bean/tapioca crisps correlates very well (r2 = 0.99) with the predicted linear expansion based on the amylopectin content of the combined flours. Legume crisps, being high in protein and fibre, are a possible cheup alternatiue to fish crisps for the production of a nutritious snack food for growing children.